2012
DOI: 10.1038/jid.2012.167
|View full text |Cite
|
Sign up to set email alerts
|

Genetics of Psoriasis: Evidence for Epistatic Interaction between Skin Barrier Abnormalities and Immune Deviation

Abstract: Psoriasis was until recently regarded as a T-cell-driven disease with presumed (auto)immune mechanisms as its primary cause. This view was supported by clinical data and genetic studies that identified risk factors functioning in adaptive and innate immunity, such as HLA-C*06, ERAP1, the IL-23 pathway, and NF-k B signaling. Candidate gene approaches and genome-wide association studies, however, have identified copy number polymorphisms of the b-defensin cluster and deletion of late cornified envelope (LCE) 3B … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
65
0
5

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
3
2

Relationship

1
9

Authors

Journals

citations
Cited by 102 publications
(71 citation statements)
references
References 108 publications
1
65
0
5
Order By: Relevance
“…Secondarily, the epidermis itself produces a range of cytokines and chemokines that help maintain the disease (3)(4)(5)(6)(7)(8)(9)(10)(11). While copy number polymorphisms in the β-defensins and deletions of the LCE3C/B locus have been associated with psoriasis (12), a primary role for epidermal defects in the pathogenesis of psoriasis is controversial. In particular, it is unknown whether epidermal repair pathways play important roles in the disease and whether such pathways interact with infiltrating immune cells.…”
Section: Introductionmentioning
confidence: 99%
“…Secondarily, the epidermis itself produces a range of cytokines and chemokines that help maintain the disease (3)(4)(5)(6)(7)(8)(9)(10)(11). While copy number polymorphisms in the β-defensins and deletions of the LCE3C/B locus have been associated with psoriasis (12), a primary role for epidermal defects in the pathogenesis of psoriasis is controversial. In particular, it is unknown whether epidermal repair pathways play important roles in the disease and whether such pathways interact with infiltrating immune cells.…”
Section: Introductionmentioning
confidence: 99%
“…HLA-C*06 in PSORS1 and deletion of the late cornified envelope (LCE) 3B and 3C genes (LCE3C-LCE3B-del) in PSORS4 are known genetic risk factors for this disease (2). The LCE gene family consists of 18 members divided into six groups LCE1-LCE6 (3), which are located on chromosome 1q21 in a region called the epidermal differentiation complex (4).…”
Section: Introductionmentioning
confidence: 99%
“…The skin barrier function results from the physical properties of the outer layer of the epidermis, the stratum corneum, which exists out of terminally differentiated keratinocytes [1,2]. Recently, research showed that the epidermal compartment, in more particular the skin barrier function, is involved in the pathogenesis of immune-mediated skin disorders such as atopic dermatitis [3] and psoriasis [4]. In addition, some skin diseases such as lichen planus, vitiligo and psoriasis arise at sites of a disrupted skin barrier, which is known as the Koebner phenomenon [5].…”
Section: Introductionmentioning
confidence: 99%